The effects of pinning on critical currents of superconducting films - Simões, R. P. [UNESP]; Venegas, Pablo Antonio [UNESP]; Mello, Denise Fernandes de [UNESP] (Springer Nature, 2013)
Using molecular dynamics simulations, we analyze the effects of artificial periodic arrays of pinning sites on the critical current of superconducting thin films as a function of vortex density. We analyze two types of periodic pinning array: hexagonal and Kagomé. For the Kagome pinning network we make calculations using two directions of transport current: along and perpendicular to the main axis of the lattice. Our results show that the hexagonal pinning array presents higher critical currents than the Kagomé and random pinning configuration for all vortex densities. In addition, the Kagomé networks show anisotropy in their transport properties. © 2012 Springer Science+Business Media, LLC.
Keywords: Kagomé lattice; Periodic pinning; Superconductivity; Vortex dynamics; Molecular dynamics simulations; Periodic arrays; Periodic pinning arrays; Pinning arrays; Transport currents; Vortex densities; Molecular dynamics; Transport properties; Vortex flow; Critical currents